Immunological evaluation of some antigens of Lucilia sericata larvae - Mohamed, Hoda S. (J Parasit Dis, 2017)
The present study aimed to select an antigen of Lucilia sericata larvae showing both high antigenicity and cross-reactive binding abilities with other related antigens of L. sericata larvae for obtaining a promising candidate vaccine antigen. The ELISA results primary concluded that among the excretory secretory (ES) and midgut (MG) antigens of the different larval instars of L. sericata, MGL2 could be characterized as antigen which was able to reflect the highest level of antigenicity and cross-reactivity with the other tested L. sericata antigens. The results were extended to spot the light on the relation between different protein bands in MGL2 and rabbit hyper- immune sera (HIS) raised against the other tested antigens using SDS-PAGE and Western blot technique. Analysis by SDS-PAGE of ES and MG antigens of the different larval instars of L. sericata revealed common protein bands at molecular weights of about 10, 12, 16, 20, 28, 33 and 46 kDa. Western blotting of MGL2 antigen transferred to nitrocellulose sheet revealed reaction by MGL2 HIS to five polypeptide bands; 20, 28, 33, 46 and 63 kDa. Three bands of 28, 33 and 63 kDa were the most prominent bands detected whereas; there was a weak reaction with bands of 20 and 46 kDa. But what was apparent in Western blot was a strong reaction of all tested HIS with a polypeptide band of 63 kDa. This band might be considered to be the main cause of cross reactive binding ability of MGL2 antigen that had been recorded previously in ELISA technique.